2016
DOI: 10.1007/s12028-016-0349-4
|View full text |Cite
|
Sign up to set email alerts
|

Clevidipine Versus Nicardipine for Acute Blood Pressure Reduction in a Neuroscience Intensive Care Population

Abstract: There were no statistically significant differences in acute BP management between the two agents; however, there was a trend toward shorter time to target and significantly less volume administered in the clevidipine group. Either agent should be considered a viable option in a NSICU population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Mean (SD) admission to administration time was 56 (22) minutes in the CLEV group and 59 (25) minutes in the NIC group (P ¼ .684). 150 (23) 142 (24) .020 Percent change between initial and final SBP (%)…”
Section: Resultsmentioning
confidence: 99%
“…Mean (SD) admission to administration time was 56 (22) minutes in the CLEV group and 59 (25) minutes in the NIC group (P ¼ .684). 150 (23) 142 (24) .020 Percent change between initial and final SBP (%)…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that nicardipine use was associated with less BPV and a higher likelihood to achieve an SBP goal lower than 140 mm Hg. Clevidipine and nicardipine were compared in a retrospective analysis of 57 neurocritically ill patients . The investigators found no significant difference in the time to target SBP or percentage time within target BP range between both groups, but nicardipine administration was associated with a higher volume infused.…”
Section: Blood Pressure Control In Neurologic Emergenciesmentioning
confidence: 99%
“…Clevidipine is a newer dihydropyridine calcium channel blocker which is also included as a treatment modality in the AHA 2018 guidelines (16). Similar to nicardipine, clevidipine generally does not decrease heart rate and in retrospective analysis has similar efficacy in lowering BP though requires less volume to be administered which may be optimal in patients with volume overload (104, 105). Since clevidipine is formulated in a lipid emulsion, there is an inherent risk of hypertriglyceridemia and pancreatitis for which there is a recommended a daily maximum of 1,000 mL (or about 21 mg/h per day) (106).…”
Section: Pharmacologymentioning
confidence: 99%